Remote Sensing Applications in Coastal Environment - Terefenko, Paweł; Lubczonek, Jacek; Paprotny, Dominik (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Coastal regions are susceptible to rapid changes, as they constitute the boundary between the land and the sea. The resilience of a particular segment of coast depends on many factors, including climate change, sea-level changes, natural and technological hazards, extraction of natural resources, population growth, and tourism. Recent research highlights the strong capabilities for remote sensing applications to monitor, inventory, and analyze the coastal environment. This book contains 12 high-quality and innovative scientific papers that explore, evaluate, and implement the use of remote sensing sensors within both natural and built coastal environments.